Causal fermion systems as a candidate for a unified physical theory. (June 2015) - Finster, Felix; Kleiner, Johannes
Abstract: The theory of causal fermion systems is an approach to describe fundamental physics. Giving quantum mechanics, general relativity and quantum field theory as limiting cases, it is a candidate for a unified physical theory. We here give a non-technical introduction.